On Random Topological Structures - Ravi P. Agarwal; Yeol Je Cho; Reza Saadati (Abstract and Applied Analysis)
We present some topics about random spaces. The main purpose of this paper is to study topological structure of random normed spaces and random functional analysis. These subjects are important to the study of nonlinear analysis in random normed spaces.